Comprehensive analysis of ferroptosis-related genes reveals potential therapeutic targets in osteoporosis patients: a computational analysis and in vitro experiments - Chen, Sihui; Jiang, Yi; Xie, Guoqin; Wu, Peng; Zhu, Jinyu (Frontiers in Genetics, 2025)
BackgroundFerroptosis-related genes have been reported to play important roles in many diseases, but their molecular mechanisms in osteoporosis have not been elucidated.MethodsBased on two independent GEO datasets (GSE35956 and GSE35958), and GSE35959 as the validation dataset, we comprehensively elucidated the pathological mechanism of ferroptosis-related genes in osteoporosis by GO analyses, KEGG analyses and a PPI network. Then, We used Western Blot (WB) and Quantitative real-time polymerase chain reaction (qPCR) to verify the expression level of KMT2D, a ferroptosis-related hub gene, in clinical samples. Subsequently, we predicted the upstream miRNA of KMT2D gene and analyzed the mechanism of KMT2D in osteoporosis, the potential prognostic value and its immune invasion of KMT2D in pan-cancer.ResultsThis study identified KMT2D and MYCN, TP63, RELA, SOX2, and CDKN1A as key ferroptosis-related genes in osteoporotic cell aging. The independent dataset validated that the expression level of KMT2D was significantly upregulated in osteoporosis samples. The experimental verification results of qPCR and WB indicate that KMT2D is highly expressed in patients with osteoporosis. Further analysis revealed that the hsa-miR-204-5p-KMT2D axis may play an important role in the aging of osteoporotic cells. The analysis of KMT2D reveals that KMT2D may mainly play a role in the aging of osteoporotic cells through epigenetics and the value in pan-cancer.ConclusionThe study provides a theoretical basis for the treatment of osteoporosis.